La valeur Gaïa - Alexander Federeau (VertigO, 2020)
The various approaches to environmental ethics are ill adapted for global environmental issues. By assigning moral values to living beings, or ecosystems, they show a concern for local or even regional issues. The article defends a new type of moral value. The Gaia value is based on the knowledge acquired through the Gaia hypothesis and the Earth system sciences to valorise the physical, chemical and biological processes that regulate and stabilise the biogeochemical cycles. As an example of how the Gaia value can be applied, the article focuses on the roles played by microorganisms in these regulations. While the microcosm is the genuine basis of life, the article shows that our ethical frameworks, even environmental ethics, do not permit us to value the microscopic world and its contributions. No microscopic species is protected, and anthropocentric, biocentric or ecocentric approaches do not value them. The Gaia value is an answer to this, as it highlights the biospheric services given by some micro-organisms.